Generation of coherent confined acoustic phonons by drifting electrons in quantum wire - Demidenko, A.A.; Kochelap, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We developed a quantum theory of generation of coherent confined acoustic phonons by one-dimensional electrons drifting in a quantum wire. A general formula for the factor of amplification of the phonon flux, α, is derived. When the electron drift velocity, Vd, is greater than the sound phase velocity, S, then at low temperatures the above generation occurs only in a narrow range of phonon wave vectors, q ~ 2kF[1 ± (Vd – S)/VF], where kF (VF) is the wave vector (Fermi velocity) of one-dimensional electrons. Estimation gives for α the value of about 10³cm⁻¹ in the subTHz frequency range.